2007
DOI: 10.1111/j.1471-6402.2007.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Psychometric Evaluation of the Interpersonal Sexual Objectification Scale

Abstract: This study reports on the development and psychometric evaluation of the Interpersonal Sexual Objectification Scale (ISOS). Data from 576 college women were collected in three studies. Exploratory factor analysis uncovered two factors: Body Evaluation and Unwanted Explicit Sexual Advances; confirmatory factor analysis supported this factor structure. ISOS scores were internally consistent and stable over a 3-week period. Supporting its construct validity, ISOS scores were (a) strongly related to sexist degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
391
6
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(422 citation statements)
references
References 34 publications
17
391
6
8
Order By: Relevance
“…At the end of the study, participants were asked to indicate whether their partner engaged in the following nonverbal behaviors on a 7-point Likert-type scale, ranging from 1 (extremely disagree) to 7 (extremely agree): smiled frequently, leaned forward while we were talking, seemed preoccupied with how I looked rather than what I was saying (modified from the Interpersonal Sexual Objectification Scale, Kozee et al, 2007), made notes of what I was saying, responded supportively to my answers, acted in a professional way, and touched me on the leg or arm. They were also asked to write the gist of the feedback they received from their partner.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…At the end of the study, participants were asked to indicate whether their partner engaged in the following nonverbal behaviors on a 7-point Likert-type scale, ranging from 1 (extremely disagree) to 7 (extremely agree): smiled frequently, leaned forward while we were talking, seemed preoccupied with how I looked rather than what I was saying (modified from the Interpersonal Sexual Objectification Scale, Kozee et al, 2007), made notes of what I was saying, responded supportively to my answers, acted in a professional way, and touched me on the leg or arm. They were also asked to write the gist of the feedback they received from their partner.…”
Section: Methodsmentioning
confidence: 99%
“…The latter part of the objectifying gaze manipulation is consistent with recent considerations of ''complimentary'' sexual objectification. Although most previous research has focused on critical forms of objectification (e.g., rude body-related comments; Gapinski, Brownell, & LaFrance, 2003;Kozee et al, 2007), Calogero et al (2009) found that weight-related compliments were associated with positive moods but also with body surveillance and body dissatisfaction. Tiggemann and Boundy (2008) also found that clothing-related compliments caused more body shame.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is known as the "objectifying gaze" (Kaschak, 1992) and represents an important channel through which objectification is perpetuated and communicated to targets (Fredrickson & Roberts, 1997;Kozee, Tylka, Augustus-Horvath, & Denchik, 2007). This objectifying gaze can be operationalized as attending to other's bodies more and faces less (Gervais, Holland, & Dodd, 2013).…”
Section: Appearance-focus Increases the Objectifying Gaze Toward Menmentioning
confidence: 99%